3D Simulation Methodology for n-Butanol Combustion in an optical accessible research GDI Engine. (September 2017) - D'Orrico, Fabrizio; Berton, Andrea; Sideri, Matteo
Abstract: The strict political regulations in terms of engine tailpipe emissions and reduction of fossil fuel dependency are pushing forward the study of alternative fuels; these fuels must be suitable for currently available engines, in order to allow quick and inexpensive replacement. The alternative fuel chosen for this analysis is n-Butanol; being its key physico-chemical properties similar to those of commercial Gasoline, it does not require relevant changes in engine design and operation and therefore it is suitable for currently produced units. The paper describes the modeling and characterization of spark-ignited combustion of n-Butanol in comparison with that of conventional Gasoline. The comparison is made by means of 3D CFD simulations and experimental tests, carried out on a single-cylinder optically accessible engine characterized by a flat and transparent piston. The engine is equipped with direct injection and makes use of a current production engine head. The operating conditions used in the experiments are reproduced in the CFD simulations, in order to validate the CFD model and to provide additional insight to the experimental observations. The numerical simulation outcomes replicate with a good accuracy the experimental test results and they help to better understand the behavior of the alternative fuel during the combustion process. The adopted modelling methodology can therefore be used for further investigations such as exploration of different engine operations through virtual DOE of both operating and functional parameter variations.